Impacts of the Techno Gabay Program in Eastern Visayas, Philippines as revealed by stakeholders’ stories of significant change - Cagasan, Editha G.; Velasco, Ma. Theresa H. (Annals of Tropical Research, 2009)
Monitoring of the impacts of the Techno Gabay Program (TGP) using the most significant change (MSC) technique was done for one year in nine Techno Gabay (TG) centers in Eastern Visayas, Philippines. Field technicians of the TG centers were trained on how to collect and select ‘stories of change’ from the TGP clients and other stakeholders. The collected stories were analyzed to determine the themes of the reported changes. The levels to which the reposted changes correspond were determined using Bennett’s hierarchy of program outcomes as a guide. A total of 80 stories were collected. These were about improvements in the field technician’s extension delivery capability, changes in the program beneficiaries’ lives, improvements in stakeholders’ knowledge, attitudes and skills and about other changes. Analysis of the MSC stories revealed that the TGP was able to cause changes corresponding to higher levels of Bennett’s hierarchy of program outcomes. This suggests that the TGP was already able to have an impact on the knowledge, attitudes, skills. Behavior, and the economic and social conditions of the program stakeholders.